Preference of mobile fitness application on skill related fitness component among varsity student / Nur Asyikin Azman - Azman, Nur Asyikin (Faculty of Sports Science and Recreation, 2018)
Purpose of this study was to find the Preference of Mobile Fitness Application on Skill Related Fitness Component among Varsity Student. The total subject involved in this study were 350 participants from two IPTA and two IPTS University which was Universiti Sains Malaysia (USM), Politeknik, KDU University College and Segi College. This study used pilot questionnaire and give to twenty five students from UiTM Jengka, Pahang before proceed to actual study. The Cronbach Alpha from pilot study is valid which (0.92). This study used online questionnaire to distribute to all participants from two IPTA and two IPTS. Result showed the most preference for both gender on skill related fitness prefer power (F=87) for first ranking and the six ranking is coordination (F=lOl). The most exercise preference for power is squat jump (3.89 ± .755), but both gender shown they prefer the different exercise in power which are for female is squat jump (3.87 ± .752) and for male is variation push up (3.99 ± .744). It is concluded, previous study stated that power is the main and important component for variation sport.